Correlation between Epidermis Thickness, Leaf Trichome Length and Density with the Whitefly Bemisia tabaci Population on Five Local Soybean Cultivars - Muhamad Lutfi; Purnama Hidayat; Nina Maryana (Universitas Gadjah Mada, 2019)
Soybeans compsumsion in Indonesia is about 2.7 million ton, while the national production is only about 0.7 million ton per year. There are some problems in the soybean production in Indonesia, including pests and diseases. Whitefly, Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), is one of the important pests in soybeans causes a significant loss of yields. Developing soybean cultivars resistant to whitefly is one of method to reduce the production loss. This study aimed to determine the relationship between the physical characteristics of lower surface leaves and B. tabaci population on five local soybean cultivars. The experiments were conducted in the IPB greenhouse by Completely Randomized Design (RCD) using five soybean cultivars (Anjasmoro, Dena-1, Detam-3, Devon-1, and Wilis) with 3 replicates. Three plants of each cultivar were planted in a polybag, put under a cage, and after one week then infested with 5 female whiteflies. The parameters observed in this study were leaf epidermal thickness; density and length of trichome on lower leaf surface; and the number of egg, nymph, and adult of the whitefly. Observations were carried out every week, from 1−7 weeks after the plant was infested with the whitefly. The population of whitefly was affected by trichome density and length, as well as by the epidermal thickness of the lower leaf surface. The infestation of B. tabaci was higher in the soybean cultivars with denser and longer leaf trichomes, and thinner epidermal of the lower leaf surface. This result of this research suggests that it is necessary to include the characteristics of leaf trichome and epidermal thickness in the breeding program to produce soybean cultivars that are superior in productivity and resistant to whitefly.